Editorial Vol.5(1) - Joshi, Dipak Raj (Contemporary Research: An Interdisciplinary Academic Journal, 2021)
If anyone is willing to take part in our publishing system as Editor or Reviewer, please let us know. Let's all work together and establish this journal system into a trusted and reputed platform.